Thermo Structural Analysis on Cylinder Head of 4 Stroke VCR Diesel Engine - Dr. K Satyanaraya; A Swathi (International Journal of Engineering and Management Research, 2020)
The main aim of the project is to analyse the design performance of VCR 4 stroke Diesel engine cylinder head at the compression ratio 16.5 using Ansys software. The basic modelling is done on CATIA V5 software. The design exposition can be done structurally and thermally in ansys. By the structural analysis the maximum and minimum von misses stress, total deformation can be determined, the maximum gas pressure required for this analysis is taken from the experimental set up of VCR engine. With the steady state thermal analysis we will get the maximum temperature distribution and total heat flux of the cylinder head with the initial pressure value. The results of both the expositions are used to decide the critical areas of the cylinder head which require further amendment and also the quality of design. If the maximum stress is less than the material strength of the cylinder head then the basic design criteria can be achieved.